Proceedings of the Tenth International Conference on Learning Analytics &Amp; Knowledge 2020
DOI: 10.1145/3375462.3375478
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and expectations about learning analytics from a brazilian higher education institution

Abstract: Several tools to support learning processes based on educational data have emerged from research on Learning Analytics (LA) in the last few years. These tools aim to support students and instructors in daily activities, and academic managers in making institutional decisions. Although the adoption of LA tools is spreading, the field still needs to deepen the understanding of the contexts where learning takes place, and of the views of the stakeholders involved in implementing and using these tools. In this sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Our review did not reveal papers suggesting the analysis of school context, which is considered a critical activity to ensure successful learning analytics adoption (Gasevic et al, 2019;Falcão et al, 2020;Tsai et al, 2021a). In general, the papers retrieved in this review did not include the stakeholders in the process of creating analytic models, tools, and systems, even the ones focusing on supporting teachers (Michailidis et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our review did not reveal papers suggesting the analysis of school context, which is considered a critical activity to ensure successful learning analytics adoption (Gasevic et al, 2019;Falcão et al, 2020;Tsai et al, 2021a). In general, the papers retrieved in this review did not include the stakeholders in the process of creating analytic models, tools, and systems, even the ones focusing on supporting teachers (Michailidis et al, 2017).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, Tsai et al (2018) proposed SHEILA, a framework that guides higher education institutions in adoption of learning analytics by providing relevant instruments for involvement of relevant stakeholders and by documenting actions taken, policy questions, and challenges commonly experienced by institutions. SHEILA has widely been used across the world ( Maldonado-Mahauad et al, 2018 ; Broos et al, 2020 ; Falcão et al, 2020 ; Vigentini et al, 2020 )). Therefore, SHEILA or similar frameworks could be used as a good starting point to understand the needs of high schools regarding learning analytics.…”
Section: Discussionmentioning
confidence: 99%
“…Faculty expectations were investigated in a number of studies as shown in Table 3. Falcão et al (2020) used the supporting higher education to integrate learning analytics (SHEILA) framework as a tool to analyse stakeholders' expectations and needs in detail in terms of adoption of LA. The study used 12 interviews and 7 focus groups with students and instructors.…”
Section: Research Methodology Processmentioning
confidence: 99%
“…On the other hand, faculty have expressed their positive perception of LA from their point of view as it offered them the following advantages: self-evaluation, teaching practise improvement, students' progress tracking and determination of students' needs (West et al, 2016;Falcão et al, 2020). Despite the positive attitude towards LA, studies have also articulated the challenges that HEIs face from the stakeholders' perspective.…”
Section: Variables Influencing Awarenessmentioning
confidence: 99%
See 1 more Smart Citation